Aid to Spain by British workers' organisations
030-0196-001 AID TO SPAIN BY BRITISH WORKERS' ORGANISATIONS. British Workers' Organisations, The Labour Party and Co-operative Union, have sent recently an important quantity of FOOD through Fondo de Solidaridad Internaciónal, which has been distributed in the following way:- SALT COD. 100 bundles Asistencia Social de la Generalidad. 50 " Gobernador Civil de Valencia. 50 " Consejo Municipal de Madrid. 50 " Hospital Militar de Onteniente. 30 " Ministerio de Trabajo y Asistencia Social. 10 " Consejo Municipal de La Carolina. 5 " Asistencia Social de Gerona. 10 " Consejo Provincial de Madrid. 2 " Colegio de Huerfanos de Ferroviarios (Arbós) (College of Railway Workers' Orphans). 4 " Asistencia Social de Lérida. 4 " Colonia de Niños Refugiados (Villanueva y Geltrú) . 2 " 66 Brigada Mixta (Sector del Centro). LENTILS. 75 sacks Asistencia Social de la Generalidad de Cataluña, 10 " Consejo Municipal de la Carolina. 10 " Asistencia Social de Gerona. 10 " Consejo Provincial de Madrid. 2 " Colegio Huerfanos Ferroviarios (Arbós). 2 " Colonia de Niños Evacuados (Villanueva y Geltrú). CORNED BEEF. 170 boxes to Asistencia Social de la Generalidad de Cataluña. CONDENSED MILK. 3,500 boxes to Asistencia Social de la Generalidad de Cataluña. 3,500 " " Consejo Municipal de Madrid. SOAP. 68 boxes Hospital Militar de Onteniente. 10 " Obreros Siderúrgica de Sagunto (Miners and mechanics) 15 " Elota (sailors) Republicana de Cartagena. 100 " Misisterio de Trabajo y Asistencia Social. 130 " Sanidad Militar. (Military Health Dept.) 50 " Sanidad de Carabineros. (Coast Guards' Health Dept,) Several bales of old CLOTHES to Asistencia Social de la Generalidad de Cataluña. Copied FC. 4/3/38. 292/946/30/196